The Impact of The Problem-Based Learning Model on Student Error Reduction in Integrated Social Science Learning - Azis, Daska; Furqan, M. Hafizul; Kamza, Muhjam; Pramono, Annisa Fitri (Jurnal Basicedu, 2023)
The misconceptions that occur in integrated social studies subjects are caused by the wide scope of material, which causes students to have difficulty understanding the concepts conveyed by the teacher. A misperception is an error in understanding and explaining a concept based on previous experience. This study aims to determine the effect of the problem based learning model on reducing students' misconceptions in integrated social studies subjects. This type of research is experimental and uses a one-group pretest-posttest design. The sampling technique used in this study is a total sampling technique (population research). The sample in this study was from class VIII-E MTsS Insan Qura'ni Aceh Besar, totaling 27 people. The data collection technique is in the form of giving tests to students, namely a pre-test and post-test that are equipped with a three-tier diagnostic test. The results showed that the average score of students' misconceptions on the pretest was 33.33%, and the post-test was 15.06%. So, there is a decrease in students' misconceptions after the application of the problem based learning model of 54.81%. The results of hypothesis testing in this study were obtained, so that H0 was accepted and H1 was rejected. So the hypothesis in this study is that there is a decrease in the value of misconceptions after the application of the problem based learning model. The conclusion of the study is that the application of the problem based learning model can reduce students' misconceptions in integrated social studies subjects about interaction between ASEAN countries (class VIII MTsS Insan Qur'ani Aceh Besar).